Berberine and its nanoformulations and extracts: potential strategies and future perspectives against multi-drug resistant bacterial infections - Yang, Xue; Wang, Yanfen; Li, Ling; Tang, Daiyan; Yan, Zhong; Li, MingYan; Jiang, Jiayi; Bi, Dongming (Frontiers in Microbiology, 2025)
The increasing prevalence of antimicrobial resistance (AMR) has led to the gradual decline in the effectiveness of existing antibiotics, posing a significant threat to global health. Many phytochemicals have antimicrobial activity, but few have been developed for clinical use. Berberine, an alkaloid found in various medicinal plants, has been recognized as a promising strategy to combat AMR due to its notable antimicrobial activity and role in reversing resistance. Here, we present a systematic, comprehensive and objective overview of the antimicrobial activity, mechanism of action, and limitations of berberine. Additionally, we discuss the antimicrobial efficacy of berberine extracts and nanoformulations. Berberine demonstrates broad-spectrum antimicrobial activity by inhibiting FtsZ, disrupting cell membranes and cell walls, and interfering with DNA and RNA synthesis. However, due to its low bioavailability and lack of systematic in vivo validation, the efficacy of berberine as a standalone treatment for bacterial infections requires further investigation. Nevertheless, it can serve as an antibiotic adjuvant to enhance the efficacy of conventional antibiotics and reverse AMR. Moreover, the excellent antimicrobial effects exhibited by berberine extracts and nanoformulations may overcome these limitations, representing potential future applications of berberine. In conclusion, berberine has great potential as an antimicrobial agent and antibiotic adjuvant in combating AMR, but systematic and comprehensive in vivo and clinical trials are still needed to evaluate the therapeutic efficacy of berberine and optimize its use.